2017
DOI: 10.2147/amep.s141414
|View full text |Cite
|
Sign up to set email alerts
|

Tips for using students during times of change in health care: lessons from the literature and from practice

Abstract: BackgroundIt is often said that the only constant in health care is change. While change is inevitable, implementing change in health care is complex, and health care stakeholders are often confronted by numerous barriers and challenges. Historically, students have been an integral part of the health system through aspects such as clinical placements, and hence, may play a role during times of change.AimThe aim of this study is to provide strategies for using students as positive agents of change by discussing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…This student‐led community‐based initiative was determined to be a feasible model of practice learning for physiotherapy students, addressing the requirement to include health promotion education in curricula, and providing an opportunity to engage in the delivery of health and well‐being programmes . This initiative has potential for further use across other health care programmes, where students are viewed as agents of change for health care provision …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This student‐led community‐based initiative was determined to be a feasible model of practice learning for physiotherapy students, addressing the requirement to include health promotion education in curricula, and providing an opportunity to engage in the delivery of health and well‐being programmes . This initiative has potential for further use across other health care programmes, where students are viewed as agents of change for health care provision …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they may provide opportunity for interprofessional learning with other health professions if well supported. Some guidelines exist regarding community and non‐traditional placements in health professional education; however, stakeholder opinion regarding student and service users’ experiences is limited . It is vital that these experiences are explored to identify the benefits and challenges presented by these placement models to determine their sustainability and effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Registered nurses also want recognition for the time and effort they spend being supportive of nursing students and providing them with learning opportunities. 26 Evans, Costello, Greenberg and Nicholas found that RNs can become disheartened and not want students because the extra work that goes with having a student is not necessarily acknowledged by management. 16 The literature supports the finding that RNs want some sort of acknowledgement for the additional effort and time they dedicate to being supportive of students and providing them with learning opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…Students have been an integral part of the health system and have a role in generate positive impact at community level and as agents of change directly and indirectly. 7 Their role as agents of change is by influencing knowledge, attitudes, and practices within community. 7 New students are needed as the young generation are regarded as agents of change that are responsible in educating the community as a prevention to potential health problems.…”
Section: Introductionmentioning
confidence: 99%
“…7 Their role as agents of change is by influencing knowledge, attitudes, and practices within community. 7 New students are needed as the young generation are regarded as agents of change that are responsible in educating the community as a prevention to potential health problems. Their knowledge and attitude towards homosexuality are vital in shaping opinions in the community.…”
Section: Introductionmentioning
confidence: 99%